Estudio de tres biorreguladores orgánicos en comparación con un fertilizante foliar comercial, en el cultivo de pepino (Cucumis sativus) - Holguín Cañola, Romario Vicente (2021)
The use of bioregulars in economically important crops offer a viable alternative to obtain acceptable yields and profitability, however, it is important to evaluate several of these prior to implementing them on a larger scale. Considering the above, the present investigation aimed at the effect of three organic bioregulators in comparison with a commercial foliar fertilizer, in the cultivation of cucumber (Cucumis sativus). The study was developed in the experimental campus "La María" of the State Technical University of Quevedo, located at Km 7 via Quevedo - El Empalme. Four treatments were studied: T1: Biol (50 L ha-1); T2: Manure tea (60 L ha-1); T3: worm humus leachate (240 L ha-1) and T4: Evergreen (1.5 L ha-1) under a randomized complete block design with four treatments in three replications. The results obtained showed that with the application of T2: Manure tea (60 L ha-1) it was possible to obtain both greater flowering and fruiting, with an average of 7.74 flowers of which an average of 5.33 fruits was obtained. In addition, with this treatment, higher yield and economic profitability were obtained, with 35017.44 kg ha-1 and 34.75%, respectively, as a result of the production of more fruits which in turn had greater weight. The size of the fruits was greater when applying T4: Evergreen (1.5 L ha-1), with equatorial and polar diameter of 5.52 cm, however, the fruits exhibited greater weight when applying T2: Manure tea (60 L ha-1) , with 328.21 g. Keywords: Organic biostimulants, foliar fertilization, cucumber.